2012
DOI: 10.1177/0143034312445245
|View full text |Cite
|
Sign up to set email alerts
|

‘Under the radar’: Educators and cyberbullying in schools

Abstract: Educators play an important role in preventing cyberbullying and encouraging positive online behaviour. In this article we report on the educator portion of a study of cyberbullying at two large, technology-rich secondary schools in Canada. We discuss 17 educators’ experiences with cyberbullying, their knowledge of social networking technology, the priority they place on preventing cyberbullying, and the remedies they suggest. Qualitative analyses of taped interview responses to 16 open-ended questions reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 28 publications
6
75
0
6
Order By: Relevance
“…A recent study by P. K. Smith, Kupferberg, et al (2012) found that, although many schools do have policies dealing with faceto-face bullying, very few mention cyberbullying or ways to deal with cyberbullying issues at school. Similar findings have been noted in Canada (see, e.g., Cassidy, Brown, & Jackson, 2012) and the United States (see, e.g., Orobko, 2010). Although it is clear that many schools are creating and adopting policies aimed at cyberbullying (see, e.g., Hunley-Jenkins, 2013), little research has examined the effectiveness of these policies at reducing rates of cyberbullying.…”
supporting
confidence: 85%
“…A recent study by P. K. Smith, Kupferberg, et al (2012) found that, although many schools do have policies dealing with faceto-face bullying, very few mention cyberbullying or ways to deal with cyberbullying issues at school. Similar findings have been noted in Canada (see, e.g., Cassidy, Brown, & Jackson, 2012) and the United States (see, e.g., Orobko, 2010). Although it is clear that many schools are creating and adopting policies aimed at cyberbullying (see, e.g., Hunley-Jenkins, 2013), little research has examined the effectiveness of these policies at reducing rates of cyberbullying.…”
supporting
confidence: 85%
“…Nonpunitive measures are suggested by some authors due the negative impact punishment could have on the perpetrator. Policies that encourage positive behaviors should be enforced (Bauman et al, 2013;Cassidy et al, 2012). When developing policies, school officials should be aware of the impact these policies will have on the school environment (Willard, 2011).…”
Section: Intervention Strategiesmentioning
confidence: 99%
“…Many students do not report incidences of cyberbullying to parents or educators because of the misconception that nothing can be done about it (Parris et al, 2012;Tenenbaum, Varjas, Meyers, & Parris, 2011). Schools are only beginning to include cybervictimization in their bullying prevention policies, and educators are often unsure of how to prevent or solve these issues (Cassidy, Brown, & Jackson, 2012). Compared with traditional bullying, adult intervention in cyberbullying requires a comfort and understanding of technology that can impede education on this issue (Cassidy et al, 2012;Tangen & Campbell, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Schools are only beginning to include cybervictimization in their bullying prevention policies, and educators are often unsure of how to prevent or solve these issues (Cassidy, Brown, & Jackson, 2012). Compared with traditional bullying, adult intervention in cyberbullying requires a comfort and understanding of technology that can impede education on this issue (Cassidy et al, 2012;Tangen & Campbell, 2010).…”
Section: Discussionmentioning
confidence: 99%